Suporte social e estresse parental em mães universitárias - Yamamoto, Camila Naomi (Universidade Federal de São Carlos, 2024)
Motherhood during the university journey combines two experiences that require effort and dedication, making these women go through difficulties beyond those that would be encountered in the experience of just one of these roles. The present research, therefore, aimed to identify the relationship between social support and parental stress among women who were experiencing the process of becoming a mother as university’s student. 11 women aged 21 to 24 participated. All were enrolled in an undergraduate course at a public or private higher education institution, with children up to one year old and who became pregnant while higher education students. Participants completed an online form that collected characterization data, the Perceived Social Support Scale (adult version) EPSUS-A and the Parental Stress Scale (EEPa). The results indicated that there were significant, positive and moderate correlations between parental satisfaction and affective support (r=0.639), and significant, positive and strong correlations between instrumental support (r=0.868) and total EPSUS scale score (r=0.763), corroborating with the literature, which states that social support can be a regulator of parental stress. Other influencing factors are also discussed, such as the type of university and pregnancy planning.
Social suport and parental stress and college mothers
Keywords: Maternidade; Universidade; Suporte social; Estresse parental; Motherhood; University; Social support; Parental stress; CIENCIAS HUMANAS::PSICOLOGIA